Strength and conditioning for the triple jumper - Cissik, J. M. (Strength and Conditioning Journal, 2013)
The triple jump is a complex track and field event. It requires athletes to achieve a high velocity and maintain it during its 3 phases: the hop, the step, and the jump. Triple jumpers must be good sprinters, have sound event-specific technique, and must have high levels of strength. This article reviews the event, discusses strength and conditioning needs, and provides a sample training program for the triple jump.